The Influence of Corporate Social Responsibility (CSR) Disclosures, Accounting Conservatism, and Leverage on Earnings Response Coefficient (ERC) - Aprilia, Nur Indriyani; Rahayu, Sovi Ismawati (Santoso Academy Network, 2023)
This study aims to examine the effect of Disclosure of Corporate Social Responsibility (CSR), Accounting Conservatism, Leverage, Earnings Response Coefficient (ERC) partially or simultaneously. The research method used is a quantitative research method and uses secondary data, namely manufacturing companies listed on the Indonesia Stock Exchange. The samples used were 34 companies in 2015-2019 whose acquisitions used the purposive sampling method. The analytical method used is multiple linear regression analysis technique. The results of this study, partially, Disclosure of Corporate Social Responsibility (CSR) and Accounting Conservatism affect the Earnings Response Coefficient (ERC). Meanwhile, Leverage has no effect on the Earnings Response Coefficient (ERC). Simultaneously, Disclosure of Corporate Social Responsibility (CSR), Accounting Conservatism, and Leverage affect the Earnings Response Coefficient (ERC).